Novel Insect Antifeedant and Ixodicidal Nootkatone Derivatives - Galisteo Pretel, Alberto (Biomolecules, 2019)
Naturally occurring nootkatone, with reported insecticidal and acaricidal properties, has been used as a lead to generate molecular diversity and, consequently, new insect antifeedant and ixodicidal compounds. A total of 22 derivatives were generated by subjecting this molecule to several reactions including dehydrogenation with the iodine/DMSO system, oxidation with SeO(2), epoxidation with mCPBA, oxidation or carbon homologations of the α-carbonyl position with TMSOTf (trimethylsilyl trifluoromethanesulfonate) followed by Rubottom and Dess Martin periodane oxidations, condensation with formaldehyde using Yb(OTf)(3) as catalyst and dehydroxilation using the Grieco protocol. The insect antifeedant (against Myzus persicae and Ropaloshysum padi) and ixodicidal (against the tick Hyalomma lusitanicum) activities of these compounds were tested. Compound 20 was the most active substance against M. persicae and R. padi, and twice more efficient than nootkatone in the antitick test.